Primary small cell carcinoma of the ureter: Case report and review of the literature. Issue 24 (June 2018) - Farci, Fabiola; Manassero, Francesca; Baldesi, Ramona; Bartolucci, Annamaria; Boldrini, Laura; Selli, Cesare; Faviana, Pinuccia
Abstract: Rationale: Primitive small cell carcinoma of the ureter is extremely rare, in this case report is meticulously described its aggressive clinical course and the pathological clues that help with the diagnosis. Also, a detailed table with the clinico-pathological features of analogous case reports in literature is provided. Patient concerns: A 79-year-old female presented with gross hematuria and flank pain. Diagnoses: Small cell carcinoma of the ureter. The surgical specimen showed a mixed histology of small cell carcinoma and transitional cell carcinoma; the common neuroendocrine markers (chromogranin A, synaptophysin, CD56) were positive, and vimentin and thyroid transcription factor 1 were negative. The patient had an advanced stage at presentation with regional nodes involvement (pT3N1). Interventions: Segmental ureterectomy was performed but it was only possible to administer 1 cycle of platinum-based adjuvant chemotherapy due to the rapid decline of her clinical parameters. Outcomes: The disease rapidly spread locally and metastasized. Lesson: The clinicians must be aware of this aggressive tumor with silent clinical course and advanced stages at presentation.